Domestick privacies : Samuel Johnson and the art of biography - Wheeler, David, 1950- (University Press of Kentucky, 1987)
Biography was Samuel Johnson's favorite among literary genres, and his Lives of the Poets is often regarded as the capstone of his career. The central place of biography in his oeuvre is explored in this collection of nine original essays by leading Johnson scholars. Varied in their focus and approach, the essays range from a philosophical overview of Johnson's notion of the relation between life and art, to a detailed reading of the Life of Milton, to a speculation on the value of the Lives in the classroom. Emerging clearly in the essays are the dual concerns -- artistic and intellectual.